1994
DOI: 10.1029/93wr03554
|View full text |Cite
|
Sign up to set email alerts
|

Reliability analysis of contaminant transport in saturated porous media

Abstract: An approach to probabilistic modeling of contaminant transport based on the first-and second-order reliability methods (FORM and SORM) is presented. FORM and SORM were initially developed for structural reliability applications to estimate the occurrence of low-probability events. They can be readily used with both analytical and numerical models and do not require restrictive assumptions about the problem geometry or about the properties of the media. Sensitivity information is obtained as an integral part of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(16 citation statements)
references
References 25 publications
0
14
0
2
Order By: Relevance
“…Essa defasagem estimulou estudos na área de modelagem probabilística e estocástica do fluxo de água subterrânea e transporte de contaminantes nas últimas décadas (SITAR et al, 1987;JANG et al, 1994;HAMED, 1996;LI et al, 2005;BAALOUSHA;KÖNGETER, 2006) por meio de diversos métodos, dentre eles a simulação de Monte Carlo (SMC) e métodos de confiabilidade.…”
Section: Probabilistic Analysis Of Groundwater Contamination Using Fiunclassified
See 1 more Smart Citation
“…Essa defasagem estimulou estudos na área de modelagem probabilística e estocástica do fluxo de água subterrânea e transporte de contaminantes nas últimas décadas (SITAR et al, 1987;JANG et al, 1994;HAMED, 1996;LI et al, 2005;BAALOUSHA;KÖNGETER, 2006) por meio de diversos métodos, dentre eles a simulação de Monte Carlo (SMC) e métodos de confiabilidade.…”
Section: Probabilistic Analysis Of Groundwater Contamination Using Fiunclassified
“…No transporte de contaminantes o evento de falha pode ser definido como a ocorrência de uma concentração observada (Cobservada) acima de uma concentração limite, Cobjetivo, para um tempo máximo pré-estabelecido, tanálise (SITAR et al, 1987;JANG et al, 1994;HAMED, 1996;LI et al, 2005;BAALOUSHA;KÖNGETER, 2006). Assim a função de performance torna-se:…”
Section: Função De Performanceunclassified
“…However, the accuracy and efficiency of FORM is low when there are large number of random variables involved. For example, Jang et al (1994) found that when the number of random variables are more than 100, MCS was more efficient than FORM.…”
Section: First-order Reliability Methods (Form)mentioning
confidence: 99%
“…Recently, FORM has been used in water resources engineering (Skaggs & Barry, 1997;Jang, Sitar & Kiureghian, 1994) and nuclear engineering (Cizelj, Mavko & Oppermann, 1994). In FOSM, the performance function is linearized about the mean value, which is the reason that method is not accurate and optimal for reliability analysis.…”
Section: First-order Reliability Methods (Form)mentioning
confidence: 99%
“…These secants (polynomials) approximate the model over the entire parameter space in a weighted least-square sense (compare with the best unbiased ensemble linearization approach described by Nowak (2009)). This is more beneficial to computing a tangent or local second derivatives (compare FORM, SORM methods, e.g., Jang et al (1994)) that approximate the model well just around one point in the parameter space.…”
Section: Global Sensitivity Analysismentioning
confidence: 99%